Chapter BlogRoll e risorse digitali per la Public History - Dati, Monica (Public History of Education. Teorie, esperienze, strumenti, 2022)
This paper proposes a brief review of digital resources useful for historians, scholars, professionals and students who want to approach Public History and which can offer opportunities for exploration and participation at several levels. The analysis has been divided into four parts, each starting from an exploration of the Italian context and then moving on to international resources: 1. Web spaces of national and international associations, 2. Oral History and Digital History, 3. Public History Journals , 4. Apps and Databases.